Design and construction of a thermoacoustically driven thermoacoustic refrigerator (August 2017) - Alcock, A.C; Tartibu, L.K; Jen, T.C (Proceedings of the ... Conference on the Industrial and Commercial Use of Energy (Print), 2017)
This work describes the design and construction of a standing wave Thermoacoustically Driven Thermoacoustic Refrigerator (TADTAR). The thermoacoustic cooler is proposed in this study as an alternative sustainable solution to current issues with vapor compression refrigerators, due to its environmentally friendlier attributes and its solar energy driven capabilities. However, one of the main hindrances to the expansion of this technology is its current lack of efficiency and performance closely related to the designing of the device. Hence, a model has been designed and constructed to perform an experimental investigation of the device's performance at the University of Johannesburg. This model will mainly be used to investigate the dynamics of the TADTAR arrangement. The TADTAR consists of two thermoacoustic systems namely a thermoacoustic engine coupled to a thermoacoustic refrigerator. The thermoacoustic engine consists of a heat source and a cordierite honeycomb stack which converts heat into acoustic energy. The heat pumping takes place within a thermoacoustic refrigerator. Guidance on the material selection, constraints and calculation of the geometrical configuration describing the device constitute the main contribution of this work.